Metal Organic Frameworks: Synthesis and Application - Deliyanni, Eleni (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Metal-organic frameworks are among the most promising novel materials. The concept of MOFs was first introduced in 1990. They were actually initially used in catalysis, gas separation, membranes, electrochemical sensors. Later on, they were introduced as SPE sorbents for PAHs (Polycyclic Aromatic Hydrocarbons) in environmental water samples, then the range expanded to the field of analytical chemistry, both in chromatographic separation and sample preparation, with great success in, e.g., SPE and SPME (Solid Phase Mico-extraction). Since then, the number of analytical applications implementing MOFs as sorbents in sorptive sample preparation approaches is increasing. ?his is reinforced by the fact that, at least theoretically, an infinite number of structures can be designed and synthesized, thus making tuneability one of the most unique characteristics of MOF materials. Moreover, they have been designed in various shapes, such as columns, fibers, and films, so that they can meet more analytical challenges with improved analytical features.Their exceptional properties attracted the interest of analytical chemists who have taken advantage of the unique structures and properties and have already introduced them in several sample pretreatment techniques, such as solid phase extraction, dispersive SPE, magnetic solid phase extraction, solid phase microextraction, stir bar sorptive extraction, etc.